Effectiveness of Corruption Eradication Commission (KPK) in Handling Corruption Crime in Indonesia - Widijowati, Dijan; Hartono, Bambang (International Journal of Psychosocial Rehabilitation, 2020)
The effort to eradicate corruption in Indonesia is not a new issue. Corruption is an extraordinary crime and also a crime against humanity, therefore corruption is a special concern for the country. The hopes of the Indonesian people to live in a country free of corruption are largely dependent on the Corruption Eradication Commission. The purpose of this study is to explore how efficiently the KPK is handling corruption cases in Indonesia. This study uses a qualitative juridical analysis method research method, which is a research method that starts from the norms, principles and regulations that exist as positive legal norms which are then analyzed qualitatively. Problem formulation discussed 1. How is the effectiveness of the Corruption Eradication Commission (KPK) in dealing with corruption. 2. What are the efforts made to optimize corruption eradication. The strategy taken so that the Corruption Eradication Commission can carry out its duties effectively is to make the Corruption Eradication Commission as a guardian of good governance that is independent and independent.